Use of Time Consumption Form to Enhance Quality Education - Adhikari, Gopi Raj (Janaprakash Journal of Multidisciplinary Research, 2023)
In this modern age, the learners want practicable knowledge to adapt to the fast pace of technological modernization. This research has dealt the very concept of application of Time Consumption Form (TCF) in teaching learning program. It develops facilitators’ and learners’ awareness enhancing sustainable education exploring their ability and strengthening confidence for their all-round development. The qualitative research has been designed with the questionnaire accessing 50 respondents. The core area of the research is Janaprakash Secondary School of Pokhara-29. Primary data were collected and a body of knowledge was literature for this research, different. Different 15 questions were developed for the research. For the validity 10 secondary level experienced teachers were selected for the responses. The results show that the TCF is applicable to enhance the sustainable development of the new era through education. The study concludes that an application of TCF in teaching learning activities enhances the competence of the learners.